The Validity and Reliability Study of the Turkish Version of the General and Sport Nutrition Knowledge Questionnaire (GeSNK) - Gokensel Okta, Pinar; Yildiz, Emine (Progress in Nutrition, 2021)
Background: Since nutrition is important for success in sports, studies have been conducted for many years to investigate athletes' knowledge about nutrition. Questionnaires and scales developed to determine athletes' levels of nutrition knowledge have drawn attention. This study is the validity and reliability study of the Turkish version of the General and Sport Nutrition Knowledge Questionnaire (GeSNK).Method: This study's participants were 401 male soccer players in the Cyprus Turkish Football Association who were 10-19 years old. The GeSNK has 62 items in 2 subscales. The first subscale, general nutrition knowledge, has 29 items. The second subscale, sports nutrition knowledge, has 33 items. The reliability of the questionnaire was determined using the split-half method, Kuder-Richardson Formulas 20 and 21, and the Cronbach's alpha reliability coefficient. Item discriminating power and item discrimination index were also used. The items with an item discrimination index below 0.20 were removed from the test. The content validity of the questionnaire was determined by consulting experts.Findings: This study found a Cronbach's alpha value of 0.884, indicating that the Turkish version of the GeSNK is reliable.Conclusions: The Turkish version of the GeSNK can be used to measure athletes' nutrition knowledge levels.